2011
DOI: 10.3324/haematol.2010.034264
|View full text |Cite
|
Sign up to set email alerts
|

Survival of European patients diagnosed with lymphoid neoplasms in 2000-2002: results of the HAEMACARE project

Abstract: The European Cancer Registry-based project on hematologic malignancies (HAEMACARE), set up to improve the availability and standardization of data on hematologic malignancies in Europe, used the European Cancer Registry-based project on survival and care of cancer patients (EUROCARE-4) database to produce a new grouping of hematologic neoplasms (defined by the International Classification of Diseases for Oncology, Third Edition and the 2001/2008 World Health Organization classifications) for epidemiological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 41 publications
8
41
0
1
Order By: Relevance
“…47 In the period 2000-2002, the European database showed an RS of 49% for DLBCL, 44% for MCL and 56% for BL. 45 The Swedish Lymphoma Registry showed a similar improvement in survival for MCL: an increase in 3-year OS from 47% in the period 2000-2005 to 62% in the period 2006-2010. 49 However, compared with clinical trials, our study showed inferior survival rates for patients with DLBCL, MCL and BL, even when the same age range was analyzed and when untreated patients were excluded ( Table 2).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…47 In the period 2000-2002, the European database showed an RS of 49% for DLBCL, 44% for MCL and 56% for BL. 45 The Swedish Lymphoma Registry showed a similar improvement in survival for MCL: an increase in 3-year OS from 47% in the period 2000-2005 to 62% in the period 2006-2010. 49 However, compared with clinical trials, our study showed inferior survival rates for patients with DLBCL, MCL and BL, even when the same age range was analyzed and when untreated patients were excluded ( Table 2).…”
Section: Discussionmentioning
confidence: 68%
“…Compared with previous population-based studies in Europe and the United States, our study showed similar RS for patients with aggressive B-cell lymphoma. [45][46][47][48] For example, in the period 1973-2003, the SEER (Surveillance, Epidemiology and End Results) database showed a RS of 48% for DLBCL, 53% for MCL and 45% for BL. 47 In the period 2000-2002, the European database showed an RS of 49% for DLBCL, 44% for MCL and 56% for BL.…”
Section: Discussionmentioning
confidence: 99%
“…Zusätzlich ver wenden sie morphologische, genotypi sche, genetische und immunhistochemi sche Kriterien ebenso wie klinisches Ver halten, um die Entitäten weiter zu diffe renzieren. Die resultierenden Subkatego rien umfassen jedoch z. T. so wenige Er krankungsfälle, dass bestimmte bevölke rungsbezogene Analysen selbst auf inter nationaler Ebene problematisch bleiben [9]. …”
Section: Hintergrundunclassified
“…A recent study of 180 000 European patients with hematological lymphoid neoplasms demonstrated that the proportion with an unspecified lymphoma subtype diagnosis increased with age suggesting that the oldest age groups receive a suboptimal diagnostic workup and therefore treatment [9]. This emphasizes the need for data on incidence and prognosis among the oldest patients with hematological cancer.…”
mentioning
confidence: 99%